Case Report: Prenatal Diagnosis of a Fetus With Harlequin Ichthyosis Identifies Novel Compound Heterozygous Variants: A Case Report - Liu, Jiao; Zhang, Xingyu; Wang, Weilan; Lan, Xiaofang; Dong, Minyue; Yan, Kai; Lei, Yongliang; Chen, Penglong; Yang, Mufeng; Shan, Qunda; Jin, Chunlei (Frontiers in Genetics, 2021)
Background: Harlequin ichthyosis (HI), which is characterized by whole body hard stratum corneum, is the most server form of keratinizing disorders. ABCA12 has been identified as the major disease-causing gene of HI. Methods: A case of HI was prenatally diagnosed by ultrasound examination and genetic analysis. The fetus was found with dentofacial deformity, profound thickening of the palm and plantar soft tissues. Chromosomal microarray analysis (CMA) and whole exome sequencing (WES) were then performed to identify germ line pathogenic mutations through sampling the amniotic fluid. Candidate mutations were verified by Sanger sequencing. Results: WES identified two heterozygous frameshift mutations (p.Q719QfsX21; p.F2286LfsX6) of ABCA12 for the fetus, each of which was maternal inherited or paternal inherited. The fetus was terminated. Conclusions: Prenatal molecular diagnosis is an important approach for prevention of HI. In the study, we provided a successful case of genetic counseling for the family with HI baby.